(untitled) (Revista Científica Compendium, 2022)
The research analyzes corporate responsibility as a management tool for promoting sustainability in Small and Medium Industries (SME´s) in the municipality of Iribarren, Lara state, Venezuela. It is framed in qualitative research whose method is ethnographic. The data collection technique included field notes, semi-structured interviews with key actors. The institutional, economic, social and environmental dimensions of Sustainable Human Development were taken into account. Among the findings, it stands out that in the institutional dimension, the issue of corporate social responsibility as a management tool with a sustainable approach is being assumed in an elementary way by some SME´s. In the economic dimension, most of the managers interviewed agreed that the success of sustainable management depends on the productivity of business organizations. In the social sustainability dimension, the most emphasized element is the guarantee of respect for human rights, specifically the workers’ right to life and a decent and fair salary. The environmental dimension, was found to be the least worked and addressed in the management process of the SME´s analyzed.